Comparison of Non-Hilar Clamping Simple Enucleation and Enucleo-Re¬section of Exophytic Renal Tumors - Balasar, Mehmet; Durmus, Emrullah; Piskin, Mehmet Mesut; Karalezli, Giray; Gurbuz, Recai; Kilinc, Mehmet (Urology Journal, 2015)
urpose: To retrospectively evaluate our institutional experience with non-hilar-clamping simple enucleation (SE) and enucleoresection (ER) for the treatment of exophytic renal tumors regarding their oncological outcomes. Materials and Methods: We retrospectively evaluated patients treated between 2006 and 2013 for clinical exophytic T1-T2a renal tumors using open nephron-sparing surgery. Results: A total of 33 patients underwent SE and 39 underwent ER. The mean tumor size was 38.7 mm. None of the patients had positive surgical margins. No local recurrences were observed during the postoperative follow-up period (mean 40.7 ± 23.4 months); however, ipsilateral adrenal and contralateral kidney metastasis was detected in one of the patients. There was no statistically significant difference in the R.E.N.A.L Nephrometry Score, operative time, or intraoperative blood loss in the non-hilar-clamping SE and ER groups (P > .05). During the third postoperative month, the estimated glomerular filtration rate (eGFR) levels in the SE group were significantly reduced compared with the preoperative eGFR levels (P = .046). Conclusion: SE and ER with non-hilar clamping are safe, acceptable approaches for treating exophytic renal tumors.